Volume assessment of age-related conversion of the tympanic cavity by helical computerized tomography scanning - Kavakli, A; Ogeturk, M; Yildirim, H; Karakas, S; Karlidag, T; Sarsilmaz, M (Saudi Med J, 2004)
Objective: To investigate the right-left asymmetry, and gender and age groups differences of the tympanic cavities (TC) using the Cavalieri principle for volume calculation on temporal bone computerized tomography (CT) scans. Methods: This study was carried out over a 4-year period from 2000 to 2004 at Firat University, School of Medicine, Elazig, Turkey. The areas of the cavities were measured using trace and area measurement functions of CT scanner, and by multiplying the area by slice thickness (0.2 cm) and the volume of each slice was calculated. By summing all volumes of every slice based on the Cavalieri principle for volume calculation, the total volumes were obtained and analyzed. Results: The mean (SD) volumes of right and left tympanic cavities in males were 0.52 (0.15) versus 0.55 (0.14) cm(3) and in females were 0.45 (0.16) versus 0.49 (0.14) cm(3), and there were statistically significant differences between males and females in both right and left sides (p=0.028 and p=0.043). There was a statistically significant difference in left TC volumes between age groups (p=0.019). However, no differences by age were noted for right TC volumes (p=0.065). A strong correlation was found between right and left. volumes. However, there were no strong correlations between age and volumes of right and left cavities in both males and females, although the volumes increased by aging. Conclusion: These results should help surgeons and radiologists to update their knowledge for evaluation of the middle ear region.
Keywords: Mastoid Air Cell